The application of expanded rank-size model in Turkish urban settlements - Vedia Dokmeci; Sevkiye Sence Turk (European Regional Science Association (ERSA), 2001)
The objective of this paper is to analyze the structure of urban system in Turkey from 1980 to 1997 by using expanded rank-size model. The former studies related to rank-size model in Turkey have illustrated important hierarchical regularities in rank-size relationships. In these studies changes in city- size distributions over time examined noting differences in slope and intercept at the different points in time. Then, these results are interpreted to indicate growth (decline) in entire system of cities and the relative rates of growth (or decline) of large and small areas. However, according to the studies by Casetti, Maleki, Stephens and Holly, Strickland and Aiken, such casual inspection of coefficients can be misleading: First one is the insufficient of criteria related to identify statistically significant changes in coefficient. Second one is the obscurity of the particular dynamics of city-system change by the simple inspection of coefficients. In order to examine to strictly change in rank –size coefficient over time. In this paper, the expanded rank-size model was applied all of cities in Turkey and separately each regional level.
Keywords: 330